Damage of magnesium potassium phosphate cement under dry and wet cycles and sulfate attack. (20th June 2019) - Li, Yue; Shi, Tongfei; Li, Yaqiang; Bai, Weiliang; Lin, Hui
Highlights: Effects of dry-wet cycles and sulfate attack on MKPC were researched. Effects of fly ash and quartz sand on the damage of MKPC were tested. Performance degradation mechanism of MKPC was discussed. Abstract: Magnesium potassium phosphate cement (MKPC) produced by dead burnt magnesia (MgO) and potassium dihydrogen phosphate (KH2 PO4 ) is a rapid repairing material. In order to repair concrete structures under dry-wet cycles and sulfate attack condition, the degradation of MKPC under the dry-wet cycles in 5 wt% Na2 SO4 solution was analyzed by investigating the mass loss and compressive strength in this paper. In addition, the influences of fly ash and quartz sand on the MKPC were also discussed. The degradation mechanism of the MKPC samples and influence mechanism of fly ash and quartz sand were analyzed based on the pore structure, XRD and SEM. The mass and compressive strength of MKPC progressively decrease after dry-wet cycles. The pore structure of MKPC was optimized by fly ash; the sample with fly ash showed improved durability under dry-wet cycles. The sample with quartz sand showed poor durability under dry-wet cycles since the quartz sand led to the initial defect and interfacial transition zone in the MKPC matrix.